Astronomy - Seeds, Michael A. (Thomson Brooks/Cole, 2005)
With this newly revised 4th edition of ASTRONOMY: THE SOLAR SYSTEM AND BEYOND, Mike Seeds' goal is to help students use astronomy to understand science and use science to understand what we are. Fascinating and engaging, this text illustrates the scientific method and guides students to these fundamental questions: "What are we?" and "How do we know?" In discussing the interplay between evidence and hypothesis, Seeds provides not just facts, but a conceptual framework for understanding the logic of science. The book vividly conveys his love of astronomy, and illustrates how students can comprehend their place in the universe by grasping a small set of physical laws. Crafting a story about astronomy, Mike shows students how to ask questions to gradually puzzle out the beautiful secrets of the physical world. With the use of mathematics set off in boxes, the book's presentation is flexible and allows instructors to teach to differing student levels. This is the only Seeds text to be written using a traditional planets-first approach. The revision addresses new developments in astrophysics and cosmology, plus the latest discoveries, from Mars' buried water to proto-galaxies at the limits of the observable universe. This edition is now fully integrated with a FREE, brand-new student tutorial system. AceAstronomy is Web-based, assessment-driven, contains book-specific activities, and is completely flexible, creating a personalized learning plan based on quiz results. This superior system gives students fun, interactive learning opportunities and a greater chance for success